2022
DOI: 10.1002/nop2.1374
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative descriptive study of effective leadership and leadership development strategies used by nurse leaders in European island countries

Abstract: Aim Nurse leaders influence workplace culture; however, little is known about ethnic cultural influences on nurse leader development. This research aims to identify personal strategies promoting effective leadership by nurse leaders from European small island countries. Design Descriptive qualitative study. Methods In 2017, nineteen semi‐structured interviews with nurse leaders from England, Greece, Republic of Ireland and Malta explored leadership journeys, strategies employed to support their growth and deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Leaders influence their followers to achieve common goals (Hughes et al, 2022 ). Nurse managers are also leaders who guide, motivate and direct nurses for the best patient, nurse and organizational outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Leaders influence their followers to achieve common goals (Hughes et al, 2022 ). Nurse managers are also leaders who guide, motivate and direct nurses for the best patient, nurse and organizational outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…In a phenomenological study, the nurses stated that nurse managers' leadership style has a major impact on their satisfaction, turnover and the quality of patient care they deliver (Saleh et al, 2018 ). In another qualitative study, it was concluded that effective nurse leaders make a significant difference in transforming health care (Hughes et al, 2022 ). Besides these studies, there are valuable systematic reviews that examine the influence of leadership on nurse outcomes.…”
Section: Introductionmentioning
confidence: 99%